PEDULI KESEHATAN PEREMPUAN DENGAN DETEKSI DINI DAN UPAYA PENCEGAHAN KANKER PAYUDARA PADA REMAJA PUTRI DI PONDOK PESANTREN WIDHATUL ULUM - Masnilawati, Andi; Thamrin, Halida (Jurnal BALIRESO, 2020)
Islamic boarding schools are a form of religious education institutions. In Indonesia, the prevalence of cancer is 1.4 per 1,000 population and is the 7th cause of death (5.7%) of all causes of death. The estimated incidence of breast cancer in Indonesia is 40 per 100,000 women. The highest type of cancer in hospitalized patients in hospitals throughout Indonesia in 2010 was breast cancer (28.7%). Therefore it is necessary to understand prevention efforts and early diagnosis so that patient detection can be carried out at an early stage so that it can reduce breast cancer deaths. Breast cancer screening is an examination or attempt to find abnormalities that lead to breast cancer in a person or group of people who have no complaints. The initial attempt to screen for breast cancer is SADARI. One of the health problems in Wihdatul Ulum Islamic boarding school, Bontokassi village, Parangloe district, Gowa district is the lack of knowledge of students on reproductive health problems, especially those related to breast cancer. The result that has been generated is an increase in knowledge where the results of the pre-test were carried out on 20 students consisting of tsnawiyah and madrasah students who were given a questionnaire with 14 questions with pre-test results, namely, 0% had good knowledge, 85% had sufficient knowledge, 5% who have less knowledge. After being given education and training at the level of natural knowledge, that is, 85% have good knowledge, 15% are sufficient and there is no one else who lacks knowledge about breast cancer.